2015
DOI: 10.1016/j.crte.2015.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of three procedures (single, sequential and kinetic extractions) for mobility assessment of Cu, Pb and Zn in harbour sediments

Abstract: The mobility of Cu, Pb and Zn in harbour sediments was investigated using single, sequential and kinetic extraction techniques. Each type of extraction provides different information on the mobility of these elements in the environment. The single HCl extraction assesses general mobility, the sequential extraction assesses geochemical partitioning and kinetic extraction allows quickly and slowly mobilized elements to be identified. Kinetic extraction also allows the influence of extraction duration to be asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 51 publications
1
15
0
Order By: Relevance
“…The lower mobility of Cu, Co, and Ni has been also reported in other studies (Fangueiro et al 2005;Chakraborty 2012). In contrast, Hamdoun et al (2015) obtained high mobility of Cu in marine sediments from Ouistreham and Concarneau Harbors (France) and Pool (UK). Leleyter et al (2012) reported high and low mobility for Pb and Zn, respectively, in estuarine sediments in France.…”
Section: Mobility Of Zn Cu Pb Co and Nisupporting
confidence: 79%
See 1 more Smart Citation
“…The lower mobility of Cu, Co, and Ni has been also reported in other studies (Fangueiro et al 2005;Chakraborty 2012). In contrast, Hamdoun et al (2015) obtained high mobility of Cu in marine sediments from Ouistreham and Concarneau Harbors (France) and Pool (UK). Leleyter et al (2012) reported high and low mobility for Pb and Zn, respectively, in estuarine sediments in France.…”
Section: Mobility Of Zn Cu Pb Co and Nisupporting
confidence: 79%
“…Metal mobility in sediments (and soils) is estimated through kinetic and sequential extraction methods (Santos et al 2010;Chakraborty 2012;Chakraborty et al 2012a, b;Hamdoun et al 2015), Diffusive Gradients in Thin Films technique, flow techniques, and Batch techniques. Each method/technique has its limits; however, combining two techniques or methods is more efficient than studying one alone (Gismera et al 2004).…”
Section: Responsible Editor: Nives Ogrincmentioning
confidence: 99%
“…However, the available heavy metal thresholds based on extractable soil metal concentrations varied more than those expressed on the basis of total soil metal (Singh et al 2011). It is difficult to evaluate extractable soil thresholds due to different extractants used for different soil types (Hu et al 2011;Hamdoun et al 2015). The extraction and determination methods of Cd and Pb are more mature than those for As (Brady et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The results can be used to predict the mobility and potential bioavailability of the metals. [16][17][18][19] The advantage of the sequential extractions is the provision of detailed information about the origins, modes of occurrence, physicochemical and biological availability, mobilization and transport of trace metals. [20][21][22][23][24][25] The technique uses reagents to carry out successive leaching of specific geochemical fractions and several different protocols are proposed in the literature.…”
Section: Introductionmentioning
confidence: 99%